Social and sustainable entrepreneurship (Advances in entrepreneurship, firm emergence and growth, 2011)
An introduction to the special volume on social and sustainable entrepreneurship / G.T. Lumpkin, Jerome A. Katz -- Creating social change out of nothing : the role of entrepreneurial bricolage in social entrepreneurs' catalytic innovations / Lisa K. Gundry, Jill R. Kickul, Mark D. Griffiths, Sophie C. Bacq -- Gaining insights from future research topics in social entrepreneurship : a content-analytic approach / David Gras, Elaine Mosakowski, G.T. Lumpkin -- Human capital and hybrid ventures / Moriah Meyskens, I. Elaine Allen, Candida G. Brush -- Understanding opportunity in social entrepreneurship as paradigm interplay / Monica Diochon, Gabrielle Durepos, Alistair R. Anderson -- Grapes, dimes, salt, and markets : social entrepreneurship and non-violent social change / J. Howard Kucher -- A process model of social intrapreneurship within a for-profit company : first community bank / Donald B. Summers, Bruno Dyck -- Social enterprise education : new economics or a platypus? / Yaso Thiru -- Distinctions not dichotomies : exploring social, sustainable, and environmental entrepreneurship / Neil Thompson, Kip Kiefer, Jeffrey G. York -- What should be the locus of activity for sustainability? : eight emerging ecologies of action for sustainable entrepreneurship / Benyamin B. Lichtenstein -- Thinking 'sustainably' : the role of intentions, cognitions, and emotions in understanding new domains of entrepreneurship / Norris Krueger, David J. Hansen, Theresa Michl, Dianne H.B. Welsh